Revolution as a «shock» of history: philosophical- historical concept of W. Benjamin - Sidorenko, Irina N. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article is devoted to analysis of the project of the revolutionary transformation of history by Walter Benjamin, in which the revolution is understood as a gap of the causal history and as the main cause of the destruction of the official history of the ruling class. The author of this article reveals that the history in Benjamin’s concept is presented as text, and the revolution is presented as a creative act that erases the dominant text of history and produces a new text as a redemption of the past, however, the revolution is doomed to failure, if there is mystification and indoctrination of the past, whereby it is transformed from a creative act in a totalitarian grip. The author of this article argues that the project of the revolutionary transformation of history by Benjamin has explanatory potential for the disclosure of the essence not only of the revolutions of the last century, but also for the understanding of such modern phenomenon as «color revolutions».